Hubungan Pencarian Informasi Lee Jeno pada Akun Twitter @LeeJeno_IDN dengan Kebutuhan Informasi Followers - Salsabilla Nafiisah (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Information seeking activities are also usually carried out to meet the needs of each individual and on this activity can be done on social media especially Twitter. Purpose Research. This study aims to find out whether there is a significant correlation between information seeking with the fulfillment information of cognitive needs, affective needs, social integrative needs, and escapist needs of @LeeJeno_IDN’s followers. Methods. This research used correlational quantitative method by using Pearson Correlation. On this population of this research were the followers themselves and got drawn sample with amount 100 using Simple Random Sampling. Result. And the result of this research shown that there is a significant correlation between information seeking with the fulfillment information of cognitive needs, affective needs, social integrative needs, and escapist needs of @LeeJeno_IDN’s followers. Keywords: Information Seeking, Information Needing, Twitter, Social Media, Information